INITIAL ANALYSIS OF STUDENTS' SCIENTIFIC LITERACY ON DYNAMICS OF PARTICLE MOTION - Putri, Mayang Wahyuni (Physics Learning and Education, 2024)
One of the most important abilities in the 21st century is scientific literacy. This research is to analyze students' initial physics science literacy abilities in the dynamics of particle motion. The research method used was descriptive quantitative with a sample of 30 students of class XI phase F.7 at SMAN 2 Solok. Data processing is obtained from two categories, namely student tests and teacher questionnaires. From the results of the student test analysis, the indicator for explaining phenomena scientifically is 61% in the "medium" category, the indicator for interpreting data and scientific evidence is 30% in the "very low" category and the indicator for evaluating and designing scientific investigations is 17% in the category “very low”. The overall average in the category of achievement of students' scientific literacy skills is 36% in the "very low" category. The results of the teacher questionnaire on the aspect of the teacher's use of learning models are 26% in the "Rarely" category, the aspect of identifying students' scientific literacy in the material on the dynamics of particle motion is 44% in the "sometimes" category, the aspect of the use of teaching materials and digital learning media is 26% in the "Rarely" category, aspects of carrying out experiments on the dynamics of particle motion, namely 3% in the "Never" category and aspects of the use of facilities and equipment, namely 21% in the "sometimes" category. Based on these results, it can trigger students' low scientific literacy abilities.